A constraint and position identification (CPI) approach for the synthesis of decoupled spatial translational compliant parallel manipulators. (August 2015) - Li, Haiyang; Hao, Guangbo
Abstract: This paper introduces a screw theory based method termed constraint and position identification (CPI) approach to synthesize decoupled spatial translational compliant parallel manipulators (XYZ CPMs) with consideration of actuation isolation. The proposed approach is based on a systematic arrangement of rigid stages and compliant modules in a three-legged XYZ CPM system using the constraint spaces and the position spaces of the compliant modules. The constraint spaces and the position spaces are firstly derived based on the screw theory instead of using the rigid-body mechanism design experience. Additionally, the constraint spaces are classified into different constraint combinations, with typical position spaces depicted via geometric entities. Furthermore, the systematic synthesis process based on the constraint combinations and the geometric entities is demonstrated via several examples. Finally, several novel decoupled XYZ CPMs with monolithic configurations are created and verified by finite elements analysis. The present CPI approach enables experts and beginners to synthesize a variety of decoupled XYZ CPMs with consideration of actuation isolation by selecting an appropriate constraint and an optimal position for each of the compliant modules according to a specific application. Highlights: A systematic approach is proposed to design XYZ compliant parallel manipulators. Screw theory is employed instead of rigid-body mechanism design experience. Constraint spaces and position spaces of compliant modules are identified. Several monolithic XYZ designs are presented using the proposed design approach.